Pengaruh Kepemimpinan, Motivasi, dan Disiplin Kerja Terhadap Kinerja Karyawan PT PAN PUTRA SAMUDRA REMBANG - Arindhita Rahmasari, Difa; Nawatmi, Sri (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This research aims to analyze the influence of leadership, motivation, and work discipline on employee performance at PT Pan Putra Samudra Rembang. The method used in this research is a quantitative approach with a survey research design. Data was obtained through distributing questionnaires to 100 employees of PT Pan Putra Samudra Rembang. The data analysis technique used is multiple regression analysis to determine the extent of the influence of each variable on employee performance. The results of the study showed that leadership had no significant statistical effect on employee performance, while motivation and work discipline had a positive and significant effect. These findings indicate that improving employee motivation and maintaining work discipline are crucial factors in enhancing employee performance at PT Pan Putra Samudra Rembang. On the other hand, the lack of influence from leadership suggests that other factors, such as leadership style or organizational culture, may need to be further examined. This research provides practical insights for the company to focus on strategies that strengthen employee motivation and discipline, while also reconsidering the role of leadership in driving performance. The implications of this study can serve as a reference for human resource management practices in similar organizational contexts.